NBNLP-A Naïve Bayes-Natural language Processing algorithm for Chatbots - Bahheti, Mamta; Patra, Indrajit; Sarkar, Paramita; Sharma, Amit; Mandal, Pawan; Santhi, M. V. B. T. (2024 IEEE 4th International Conference on ICT in Business Industry & Government (ICTBIG), 2024)
In the contemporary era, a growing number of individuals engage with Information and Communication Technology (ICT) tools, witnessing the continuous expansion of technology and its diverse applications. A prevalent observation is the prevalence of virtual machines on websites, adept at responding to user queries and furnishing relevant information-these virtual entities are commonly known as Chatbots. Creating Chatbots involves leveraging a variety of programming languages, such as HTML, CSS, JavaScript, Pluto, PHP, Python, as well as incorporating elements of artificial intelligence and machine learning. Each language contributes unique features to Chatbot's functionality. This work proposes "NBNLP-A Naïve Bayes-Natural language processing algorithm for Chatbots" and provides a straightforward comparison of Chatbots developed in different programming languages, shedding light on their distinct attributes. The ensuing discussion delves into a comparative analysis of the working mechanisms and features inherent in Chatbots crafted using diverse programming languages.